HUBUNGAN PROGRAM KAMPUS MENGAJAR DENGAN KETERAMPILAN MENGAJAR MAHASISWA PGSD KAMPUS SUMEDANG - Ratih Aulia, Siti; Ahmad Syahid, Aah; Gustian Nugraha, Rana (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to determine the relationship between the Kampus Mengajar Program and the teaching skills of students of PGSD (Primary School Teacher Education) at Kampus Sumedang. The research employed a quantitative method with a correlational approach. The population consisted of PGSD students at Kampus Sumedang who participated in the 2024 Kampus Mengajar program. The research instrument was a Likert-scale questionnaire. Data were analyzed using descriptive statistics and the Spearman Rho correlation test. The results showed that the Kampus Mengajar program was categorized as “Very High,” while the students’ teaching skills were also categorized as “Very High.” The Spearman Rho correlation test yielded a correlation coefficient of r = 0.764 with a significance value of p < 0.001 (p < 0.05), indicating a positive and significant relationship between the Kampus Mengajar program and students’ teaching skills. The coefficient of determination revealed that the Kampus Mengajar program contributed 58.37% to the students’ teaching skills, while the remaining percentage was influenced by other factors. Based on these findings, it can be concluded that the better the implementation of the Kampus Mengajar program, the higher the teaching skills of PGSD students at Kampus Sumedang.